Batch Fabrication of Metasurface Holograms Enabled by Plasmonic Cavity Lithography. Issue 21 (30th August 2017) - Liu, Liqin; Zhang, Xiaohu; Zhao, Zeyu; Pu, Mingbo; Gao, Ping; Luo, Yunfei; Jin, Jinjin; Wang, Changtao; Luo, Xiangang
Abstract: Metasurface holograms consisting of nanostructures have shown great promise for various applications due to their unique capability of shaping light. Usually, they are fabricated by point‐by‐point scanning method, such as focused ion beam and electron beam lithography, which would greatly hamper their applications due to the high cost and low yield. In this work, plasmonic cavity lithography is proposed to fabricate metasurface holograms. The lithography system consists of Cr mask and plasmonic cavity that compose of 20 nm Ag/30 nm photoresist/50 nm Ag, where an air separation layer exists between them to avoid contamination and damage of mask patterns. The simulated results show that the cavity can effectively amplify the evanescent waves and modulate the electric field components on imaging plane, resulting in greatly improved resolution and fidelity compared to near field and superlens lithography. In experiments, the Au metaholograms are fabricated by the proposed lithography method and following etching processes. Furthermore, the designed holographic image of character "E" is successfully observed with the fabricated hologram. This approach is believed to open up a batch fabrication way for reproducing many copies of a metasurface hologram. Abstract : Plasmonic cavity‐lens‐based lithography is proposed for the batch fabrication of optical metasurfaces. As a proof, metasurface holograms composed of arrays of rotating apertures are fabricated by the proposed lithography technology. The proposed approach is well supported by experimental characterization of the designed sample and may find potential applications in the large‐area fabrication of functional devices.